Pharmacogenomic Considerations In Propofol: A Review - Ziske Maritska; Tri U. Pratiwi; Muhammad J. Aldwin; Clinton F.M Sitanggang; Ferdy Rahadiyan (Universitas Padjadjaran, Indonesia, 2023)
Pharmacogenomics is one of the pivotal fields of science in the era of precision medicine. It helps provide an understanding of what causes the differences in terms of pharmacokinetics and pharmacodynamics of a particular drug in patients. Hence, this leads to better efficacy. This branch of medicine also applies to sedative drugs in the anesthesia field, one of which is propofol. Changes in propofol pharmacokinetics and pharmacodynamics properties might lead to toxicity and inadequate sedation. This review wishes to better understand how pharmacogenomics is applied in anesthesia, especially in propofol, one of its most commonly used medications.